Microbial Contamination of Chicken Litter Manure and Antimicrobial Resistance Threat in an Urban Area Setting in Cameroon - Marie Paule Ngogang; Tambo Ernest; Jennifer Kariuki; Mohamed Moctar Mouliom Mouiche; Jeanne Ngogang; Abel Wade; Marianne Antonia Bernada van der Sande (MDPI AG, 2020)
We conducted a pilot study to assess microbiological safety of chicken litter, an affordable organic and main fertilizer used in Cameroon and worldwide. A convenience sampling of 26 farms was done and a questionnaire was administered. Samples of litter were aseptically collected. E. coli and Salmonella spp. were isolated using CLSI standards. Antibiotic susceptibility testing was performed using the disc diffusion method and a micro broth dilution method for colistin. In broiler farms, 90% of participating farmers gave antibiotic prophylaxis. The prevalence of E. coli and Salmonella spp. was 59.1% and 15.5%, respectively. All E. coli isolates were multidrug resistant as well as 36.4% for Salmonella spp. No resistance was found against cefepime and imipenem. All Salmonella spp. tested were found sensitive to colistin while 26.7% of E. coli spp. were colistin resistant. Contamination of chicken litter may be an underestimated source of antimicrobial resistance (AMR) transmission towards animals, humans and the environment with multidrug resistant E. coli and Salmonella spp. This shows the need and opportunity for a One Health approach in AMR surveillance and control in Cameroon. Continued surveillance in chicken litter would enable monitoring of AMR risks and trends.